Pengembangan Kapasitas dan Kelembagaan Kelompok Simpan Pinjam di Desa Sendangarum, Minggir, Sleman - Yuli Kurniyati; Bening Hadilinatih (Jurnal Maksipreneur, 2014)
Padukuhan Singojayan savings groups and Mawar savings group and loans Toglengan, village Sendangarum Minggir sub district, Sleman, has the problem: 1). The weakness of the institution ala spects of group organization, yet have a clear institutional rules, 2) Still Weak aspects of group administration, administrative and financial management systems are still very simple, 3) Low skills of administrators in the management of savings and loans, the ability of the management of the organization low group 4). The low activity of productive business (entrepreneurship) members. Metode approach used to over come the problem of partner is counseling, training and mentoring. The training consists of training the administrative and book keeping group, institutional management and Cooperative Training, Computer Training & Practice (Ms.Word & Ms Excel), entrepreneurship training and counselling on procedures for the preparation of Planning and Budgeting. Participants of the training consists of aboard of each pathners group. Activity targets are to be achieve done achactivity are as follows: 1) Extension of the procedure for the preparation of Planning and Budgeting; to improve the knowledge and ability to prepare a document for Planning and Budgeting group. 2). Administration and book keeping training group; to improve the knowledge and skills of participants in the financial administration and book keeping savings group savings and loan accounting. 3). Institutional and cooperative management training; that the boardhad knowledge of the institutional and cooperative management. 4) training and practice computer; to improve the knowledge and skills to use computers to support the administration of savings groups. 5) entrepreneurship training; to improve the understanding of entrepreneur shipand increased interest, the spirit of entrepreneurship, as well as an increase in entrepreneurial activities of the participants. While the targets to begenerated from the mentoring activities are: 1) Savings Group are orderly administration includes administrative requirements of the organization and administration book keeping.2) Enterpreneurship spirit and motivations 3). Improving the skills of administrators in operating a computer for administrative support groups. 4). Establishment of a complete annual financial statements (Balance Sheet report, Net Income Reports, Cash Flow Statement) as part of the management performance report submitted in the annual RAT5). Completion of the Planning and Budgeting, SOP savings and loans, the rights and obligations of members, management job description. This result already achieved in this activity is implemented entrepreneurship training, administration, and computer groups to improve understanding and skills committee. To each group was given the help of computer/notebook for each administrative group support. To follow up the training next plan is for mentoring activities to each groups.